Genotoxic evaluation of polystyrene microplastic - Ahmet Ali Berber (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Pollution of the aquatic environment by microplasticcould be having a massive impact on marine life. As far as the dimensions ofthe microplastics decrease, the negative effects are also increasing. In this study, the effects of 1 µm diameterpolystyrene microplastics (PSMs) on Daphniamagna and Neocaridina davidi wereinvestigated. The acute toxicity test was conducted on Daphnia magna. According to the test LC50 value wascalculated as 808.97 μg/mL. According to genotoxic evaluation on Neocaridina davidi with single cell gelelectrophoresis (Comet), tail length, tail intensity and tail moment wereincreased by PSMs compared to the control.